IoT-based Smart City with Streetlight Controlling, Drainage Overflow Alert and Vehicle Parking Management - P. V. Krishna Rao, Choppa Pallavi, Bathina Keerthi Reddy, Goda Harshitha, Devarayapalli Nandana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The world's population is increasing day by day, and with it, the number of domestic problems. To address these problems and make citizens' lives easier, we are adopting the latest technology. The world is becoming increasingly smarter and looking for secure ways to optimize resources and improve the quality of life. This need has led to the development of smart and safe cities that connect the virtual world to the physical world and provide real-time services that can be adapted to real-time situations based on IoT technology. This system uses various sensors to monitor infrastructure in a city. The system sensors are connected to an ATmega16 microcontroller using the wireless communication technology IoT. We are designing a smart city for better facilities and automatic alerts in a community. In this project, we are implementing a smart parking system, a drainage leakage system, and automatic intensity control of streetlights for power savings. Everything is updated for IoT. Water level sensors are used to alert the public to leaks; parking systems will notify the public of the status; and LDRs are used to automatically save power. All components are connected to the Arduino microcontroller. The Arduino ATMEGA328 microcontroller is used to process input and produce output using the Arduino IDE with embedded C programming. It is powered by a regulated power supply that provides 5 volts of DC voltage to all hardware modules.